Generalized effects of refrigerant charge on normalized performance variables of air conditioners and heat pumps. (April 2017) - Mehrabi, Mehdi; Yuill, David
Highlights: Normalized effects of charge variation on vapor compression systems are provided. Effects are generalized from experimental results from several systems. The normalized effects on diverse systems is sufficiently homogeneous. It is reasonable to use the models as broad predictors in many applications. Abstract: Performance degradation of air conditioners and heat pumps due to faults has been studied in several experiments reported in the literature. Among the faults, refrigerant charge variation is believed to be very common, and has been the focus of experiments by many researchers. In the current paper, using all available results in the literature, the effect of refrigerant charge faults on single-speed air-cooled air-conditioners and heat pumps is summarized. Generalized relationships have been developed to describe the fault effects, and these are provided for equipment operating at ANSI/AHRI 210/240 standard test conditions. Results are presented separately for fixed orifice (FXO) and thermostatic expansion valves (TXV), for both cooling and heating modes. The variation level of the results indicates that for many applications, it is reasonable to use these generalized relationships to estimate the effect of refrigerant charge variation on systems that have not been tested in a laboratory.